Correlation of Dental Caries Experience with pH, Buffering Capacity and Flow Rate of Saliva among 15-year-old School Children in Mangalore - Vijay S Kumar; Ganesh Shenoy Panchmal (Wolters Kluwer Medknow Publications, 2013)
Aim and Objectives: To correlate dental caries experience with pH, buffering capacity and flow rate of saliva among 15-year-old-children Materials & Method : Fifteen year old school children from adopted schools of a dental college in Mangalore were considered as study subjects. The study was carried out using a standardized proforma that consisted of questionnaire for recording demographic data. The caries experience was assessed by DMFT Index. Salivary pH was measured by using a pH meter and salivary buffering capacity was measured by using titration method. Unstimulated whole saliva was collected from all subjects by direct expectoration to calculate the flow rate. Results: The mean DMFT of the study population was 2.85 ± 2.5. The mean salivary pH was found to be 6.88 ± 0.69.About 74.1% were having medium salivary buffering capacities. The mean unstimulated salivary flow rate and mean total antioxidant capacity of the study population was 0.41 ± 0.14 ml/min and 94.15 ± 60.72 g/dL respectively. Conclusions: A marked association between the pH, buffering capacity and unstimulated flow rate with dental caries experience suggest that assessment of these salivary parameters can be used as predictors for future dental caries susceptibility in an individual.